URGENSI IZIN BELAJAR BAGI PNS YANG AKAN KULIAH (Studi Kasus di SMPN 1 Moro Kab. Karimun) - Nurazyu Kurniawan; Muhammad Arief Noor; Abdul Kohar; Arik Siswanto; Alip Farhan (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This study uses a descriptive qualitative approach, where researchers are the key instrument. The data collected were obtained from observations, interviews, and documentation. The data analysis technique used is triangulation, with the addition of several relevant sources. This study discusses the urgency of study permits for civil servants who will study. This phenomenon involves several civil servants who face obstacles in managing promotion through the diploma adjustment route due to not having a study permit issued by the Karimun Regency BKPSDM. The Regent of Karimun has issued a circular explaining the procedure for obtaining study permits for civil servants who will study. However, there are still civil servants who do not comply with these regulations and choose to continue studying without having a study permit. This phenomenon also occurs at SMPN 1 Moro, where several civil servants who have finished college but experience problems in the process of managing promotion through the diploma adjustment route. Based on this background, this study aims to explore the reasons behind the decision of civil servants to continue studying even without a study permit. From the results of the study, it was obtained that the lack of information regarding study permits and the issuance of Law number 14 of 2005 caused civil servants at SMPN 1 Moro to continue studying even without a study permit. The distance and topography separated by the ocean are also the reasons why civil servants at SMPN 1 Moro do not take care of study permits until completion. It was also found that the impact felt by civil servants at SMPN 1 Moro was not only an obstacle in class promotion, but also had an impact on periodic salary increases.